2022
DOI: 10.1111/andr.13181
|View full text |Cite
|
Sign up to set email alerts
|

Gender affirming hormonal treatment in Danish transgender persons: A nationwide register‐based study

Abstract: Background: Gender affirming hormonal treatment (GAHT) is a cornerstone in transgender care. National data are sparse regarding use of hormonal treatment by transgender persons. Aim: To assess use of GAHT in transgender persons. Design: National register-based cohort study in Danish transgender persons followed from 2000 until 2018. The main outcome measure was prescription and purchase of GAHT. Persons with ICD-10 diagnosis code of "gender identity disorder" (CGI-cohort) and persons with legal sex change but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Transgender people tend to engage with these therapies to modify their physical presentation in line with their gender identity 6,7 ; importantly, sex hormones may also affect psychological states and social interactions, as is observed during puberty 8 . However, despite the large and growing prevalence of gender-affirming hormone therapy across countries 9 , no systematic review of research has been conducted to examine the state and quality of evidence for effects of gender-affirming hormone therapy on psychosocial functioning among transgender people. Research in humans and non-human animals has suggested that hormones may influence psychosocial functioning via biological pathways [10][11][12][13] , but findings in this literature have often been mixed or inconclusive.…”
mentioning
confidence: 99%
“…Transgender people tend to engage with these therapies to modify their physical presentation in line with their gender identity 6,7 ; importantly, sex hormones may also affect psychological states and social interactions, as is observed during puberty 8 . However, despite the large and growing prevalence of gender-affirming hormone therapy across countries 9 , no systematic review of research has been conducted to examine the state and quality of evidence for effects of gender-affirming hormone therapy on psychosocial functioning among transgender people. Research in humans and non-human animals has suggested that hormones may influence psychosocial functioning via biological pathways [10][11][12][13] , but findings in this literature have often been mixed or inconclusive.…”
mentioning
confidence: 99%